Is it possible to use behavior characters for evolutionary reconstruction in marine invertebrates? A methodological approach using Ethokit logger - De Godoy, Isabela A. [UNESP]; Alberts, Carlos C. [UNESP]; Nespolo, Caio H. [UNESP]; De Oliveira, Juliana [UNESP]; Stampar, Sérgio Nascimento [UNESP] (FapUNIFESP (SciELO), 2021)
The use of behavioral data is quite common in studies of chordate animals and some groups of arthropods; however, these data are usually used in ecological and conservation studies. Their use remains uncommon in phylogenetic reconstructions, especially for non-model groups in behavioral studies. This study aims to evaluate the methodological use of behavioral (feeding process) data with EthoKit Logger in the phylogenetic reconstruction of the Cnidaria, a group in the so-called ‘lower’ Metazoa. The results indicate considerable cohesion with reconstructions based on molecular data available in previous studies. We therefore suggest that the use of behavioral characters can possible be a useful secondary tool or a proof test for molecular evolutionary reconstructions.
Keywords: Behavioral data; Feeding; Marine biology; Phylogeny